2017
DOI: 10.1002/biot.201600243
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of growth factor‐based therapeutics in vascular diseases: Challenges and strategies

Abstract: Either cardiovascular or peripheral vascular diseases have become the major cause of morbidity and mortality worldwide. Recently, growth factors therapeutics, whatever administrated in form of exogenous growth factors or their relevant genes have been discovered to be an effective strategy for the prevention and therapy of vascular diseases, because of their promoting angiogenesis. Besides, as an alternative, stem cell-based therapy has been also developed in view of their paracrine-mediated effect or ability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 156 publications
(165 reference statements)
0
5
0
Order By: Relevance
“…It was reported that even for tissue constructs bathed in culture medium with harmonic or circulatory motion in case of vibratory or rotating bioreactors respectively, diffusion is the only mechanism to control oxygen exchange inside the construct [37][38][39]. The problem of oxygen supply can be resolved by vascularization of the synthetic cardiac patch via co-culture with endothelial cells and/or release of angiogenesis growth factors [25,40]. While these neovascularization strategies have been widespread in tissue engineering, problems remain with inosculation of the in vitro formed vessels with the host vessels.…”
Section: Challenges In Cardiac Tissue Engineeringmentioning
confidence: 99%
“…It was reported that even for tissue constructs bathed in culture medium with harmonic or circulatory motion in case of vibratory or rotating bioreactors respectively, diffusion is the only mechanism to control oxygen exchange inside the construct [37][38][39]. The problem of oxygen supply can be resolved by vascularization of the synthetic cardiac patch via co-culture with endothelial cells and/or release of angiogenesis growth factors [25,40]. While these neovascularization strategies have been widespread in tissue engineering, problems remain with inosculation of the in vitro formed vessels with the host vessels.…”
Section: Challenges In Cardiac Tissue Engineeringmentioning
confidence: 99%
“…The increased accessibility and advances in chemical modifications to enhance protein half-life in vivo and minimize immunogenicity have also supported the use of growth factors/ cytokines as therapeutic targets for heart repair [106]. However, important challenges still exist in terms of ensuring the reparative mechanisms of these biomolecules and making them clinically viable [107,108], together this serves to guide the development of future growth factor formulations. Exercise training on the other hand avoids many of the issues involved with delivery of targeted therapeutics and has shown to provide beneficial effects even in the case of chronic heart failure in aged individuals [109].…”
Section: Current Clinical Evidence That Support the Use Of Non-invasimentioning
confidence: 99%
“…[6,[9][10][11][12] Still, the low half-lives and low stability of GFs in the blood flow and inside tissue-engineered scaffolds limit their application in vascular diseases. [13] In addition, adding single GFs to the cell growing in scaffolds usually leads to poorly organized and immature blood vessels. [11] Artificial in vitro systems pose a challenge as GFs have a half-life [13] of maximum 18 h in media, which thus requires close monitoring of their activity to ensure their replacement in time.…”
Section: Introductionmentioning
confidence: 99%
“…[13] In addition, adding single GFs to the cell growing in scaffolds usually leads to poorly organized and immature blood vessels. [11] Artificial in vitro systems pose a challenge as GFs have a half-life [13] of maximum 18 h in media, which thus requires close monitoring of their activity to ensure their replacement in time. [14] Multiple GFs have been found to play a role in angiogenesis and vascularization including vascular endothelial growth factor (VEGF), basic fibroblast growth factor (b-FGF), angiopoietin 1 (Ang1), and 2 (Ang2), Ephrin-B2 (Ephr), and platelet-derived growth factor (PDGF).…”
Section: Introductionmentioning
confidence: 99%